Penerimaan Gen Milenial tentang Toleransi Beragama pada Video "Loe Lihat Nih Login!! Ini Indonesia Bung!! 6 Pemuka Agama Jadi Satu di Lebaran!! – Jafar" di Kanal YouTube Deddy Corbuzier - Paramayuda Satria Oktialam; Syafrida N. Febriyanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The development of digital technology had reached the millennial generation, who were actively engaged online, although they remained vulnerable to provocative narratives, especially those related to religion-based identity politics. However, digital media also served as a positive platform, as seen in Login Season 2 Episode 30, which presented interfaith dialogue in a relaxed and communicative manner. This study examined how the millennial generation received the message of religious tolerance in the video, using Stuart Hall’s Encoding-Decoding Theory and a qualitative method through reception analysis. The results showed that most millennials were in the Dominant Hegemonic position, accepting the message of tolerance conveyed, although some were in the Negotiated position, believing that the content did not fully reflect the current social reality. The content proved to be acceptable to millennials because it was delivered in a way that aligned with their characteristics.